The association of cigarette smoking with the development and progression of diabetic retinopathy: based on cross-sectional survey and mendelian randomization - Bin Wang; Hui Li; Huafeng Ma; ZaiHong Chen (Journal of Translational Medicine)
Abstract Background The relationship between cigarette smoking and diabetic retinopathy (DR) remains controversial, as existing studies have yielded inconsistent results. This study aimed to investigate the association between smoking and both the development and progression of DR. Methods This study encompassed two complementary approaches. First, we performed a cross-sectional analysis to examine the association between smoking and DR, including its subcategories, utilizing data from the National Health and Nutrition Examination Survey. Subsequently, we implemented Mendelian randomization (MR) to explore the causal relationship between smoking and DR, as well as its specific categories, leveraging genome-wide association study data. Results The cross-sectional study found an inverse association between smoking and DR risk across three analytical models (fully adjusted OR = 0.50, P < 0.001) that still persisted after propensity score matching (OR = 0.56, P = 0.011), and MR analysis also supported this finding (OR = 0.50, P = 0.024). Subgroup analyses revealed significant protective associations in males (OR = 0.41, P < 0.001), individuals with diabetes duration ≥ 10 years (OR = 0.43, P = 0.011), and those with normal clinical parameters. After categorizing DR by severity levels, smoking showed protective associations with the onset of mild and moderate-severe non-proliferative DR in the cross-sectional study, and with the onset of proliferative DR in MR analysis (OR = 0.41, P = 0.016). However, no association was observed between smoking and DR progression. Conclusions Our findings suggest a protective association between smoking and DR development in specific subgroups across different DR stages, while showing no association with DR progression.